(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The rapid globalization of the workforce necessitates proficiency in English, particularly in professional contexts. This study examines the technologies employed in vocational schools to develop students’ professional vocabulary in English. It explores the effectiveness of digital tools, blended learning approaches, and interactive methods in enhancing language acquisition. The findings underscore the importance of integrating technology in vocational education to better prepare students for the global job market.